A popular culture study of Ricardo Grozen's 15 hiligaynon komik stories - Bagay, Floravelyn May L.
The popularity of comics had influenced both the media world and the masses itself. Because of this popularity, a mass culture sprout that resulted to the different criticisms from the critiques of popular culture. This study of Ricardo Grozen?s comic stories is presented to evaluate the popular topics usually seen in the comic stories that made it popular to the people especially to the masses and how komiks have been significant to the lives of the people according to the concepts provided by Soledad Reyes.